THE MANAGEMENT OF SOLID MEDICAL WASTE AT HOSPITAL X IN PASURUAN REGENCY DURING THE COVID-19 PANDEMIC - Frits Hendrik Kaiya; Ifit Bagus Apriantono; Candra Novi Dermawan; Cicin Ulfinah; Ahmad Yunus; Lilik Zuhriyah (Universitas Brawijaya, 2022)
Background – The COVID-19 pandemic has increased the rate of medical waste generation in hospitals. The amount of medical waste generated during the COVID-19 pandemic must be followed by the handling of solid medical waste by standard operating procedures. Improper handling of solid medical waste will harm the environment and human health. This study aimed to determine the solid medical waste management strategy during the COVID-19 pandemic. Methods – This descriptive observational study was conducted at X Hospital, Pasuruan Regency. Data was collected using observation, interviews and secondary data collection during 2020 and 2021. Interview respondents were the Head of the Medical Support Division, the K3RS and B3 Admin sections and the PPI team leader. Results – There was an increase in the amount of solid medical waste during the COVID-19 pandemic, from an average of 2,495.87 kg in 2020 and 2509.41 kg in 2021. This problem was overcome by a strategy in solid waste management during the COVID-19 pandemic. The strategy was carried out at the sorting and storage stage, namely by involving the PPI team directly in waste management and regular and scheduled training for all Hospital X staff which had not been carried out before the pandemic; at the collection stage, namely by adding garbage collection to 3 (three) times a day according to the guard shift by using PPE level 2; and the waste transportation stage, the strategy adopted is to add a third party medical waste from 1 (one) to 3 (three). Conclusion – There was a change in strategy in the management of solid medical waste at Hospital X, Pasuruan Regency during the Covid-19 pandemic, namely at the stages of sorting and storing, storing and transporting waste. However, at the temporary collection stage, there was no change. Keywords – Solid medical waste, medical waste management, COVID-19 waste.